A Sporadic Four-Year Hospital Outbreak of a ST97-IVa MRSA With Half of the Patients First Identified in the Community - Rubin, Ingrid M.; Hansen, Thomas A.; Klingenberg, Anne Mette; Petersen, Andreas M.; Worning, Peder; Westh, Henrik; Bartels, Mette D. (Frontiers in Microbiology, 2018)
This study describes a sporadically occurring four-year outbreak of methicillin-resistant Staphylococcus aureus (MRSA) originating from a surgical ward. Whole-genome sequencing (WGS) identified the outbreak clone as spa type t267, sequence type ST97 and SCCmec IVa. Prompted by the finding of four patients within six months in the same ward with this unusual MRSA type, an outbreak was suspected. Subsequent MRSA screening in the ward in February 2017 identified three additional patients and two health care workers (HCWs) with t267/ST97-IVa. WGS linked these nine isolates to 16 previous isolates in our WGS database and the outbreak thus included twenty-three patients and two HCWs. Twenty-one patients had a connection to the surgery ward during the period 2013 to 2017, but half of them had MRSA diagnosed in the community long after discharge. The community debut of several patients’ MRSA infections weeks to months after hospital discharge made the identification of a hospital source difficult and it was the SNP relatedness of the isolates that led us to identify the common denominator of hospitalization. An index patient was not identified, but our hypothesis is that HCWs with unrecognized long-term MRSA colonization could have caused sporadic nosocomial transmission due to intermittent breaches in infection prevention and control practice.